Wybrane elementy stylu życia rodziny a problem nadwagi i otyłości u dzieci w wieku wczesnoszkolnym. Doniesienie z badań = Selected elements of family lifestyle and the problem of overweight and obesity among young school children - SZYMAŃSKA, ANETA; DOBROWOLSKA, BEATA; PILEWSKA-KOZAK, ANNA BOGUSŁAWA; PAWŁOWSKA-MUC, AGNIESZKA KONSTANCJA (Journal of Education, Health and Sport, 2015)
Szymańska Aneta, Dobrowolska Beata, Pilewska-Kozak Anna Bogusława, Pawłowska-Muc Agnieszka Konstancja. Wybrane elementy stylu życia rodziny a problem nadwagi i otyłości u dzieci w wieku wczesnoszkolnym. Doniesienie z badań = Selected elements of family lifestyle and the problem of overweight and obesity among young school children. The research report. Journal of Education, Health and Sport. 2015;5(12):137-148. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35214 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A137-148 http://pbn.nauka.gov.pl/works/678478 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 25.11.2015. Accepted: 10.12.2015. Wybrane elementy stylu życia rodziny a problem nadwagi i otyłości u dzieci w wieku wczesnoszkolnym. Doniesienie z badań Selected elements of family lifestyle and the problem of overweight and obesity among young school children. The research report Aneta Szymańska1, Beata Dobrowolska2, Anna Bogusława Pilewska-Kozak3, Agnieszka Konstancja Pawłowska-Muc4 1 Szpital Neuropsychiatryczny im. prof. M. Kaczyńskiego, Samodzielny Publiczny Zakład Opieki Zdrowotnej, Zakład Opiekuńczo-Leczniczy Lublin 2 Katedra Rozwoju Pielęgniarstwa, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 3 Katedra i Klinika Ginekologii i Endokrynologii Ginekologicznej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 4 Ośrodek Kształcenia Podyplomowego Pielęgniarek i Położnych Radomski Szpital Specjalistyczny im. dr Tytusa Chałubińskiego w Radomiu Autor do korespondencji: Mgr Aneta Szymańska Szpital Neuropsychiatryczny im. prof. M. Kaczyńskiego Samodzielny Publiczny Zakład Opieki Zdrowotnej, Zakład Opiekuńczo-Leczniczy, ul. Abramowicka 2 20-442 Lublin Email: anetaszymanska3@wp.pl Słowa kluczowe: styl życia rodziny, nadwaga, otyłość, dzieci w wieku wczesnoszkolnym. Keywords: family lifestyle, overweight, obesity, young school children. Streszczenie Wstęp. Nadwaga i otyłość dzieci stanowi współcześnie jeden z poważniejszych problemów zdrowotnych, co powinno stanowić wezwanie do wielosektorowych działań m.in. z zakresu promocji zdrowia i edukacji zdrowotnej obejmujących rodziny dzieci i ukierunkowanych na zmianę stylu życia. Cel. Poznanie i analiza wybranych elementów stylu życia rodzin dzieci z nadwagą i otyłością w wieku wczesnoszkolnym. Materiał i Metoda. Badania przeprowadzono w 2015 roku wśród 75 rodziców (100%) dzieci w wieku wczesnoszkolnym z nadwagą lub otyłością, uczęszczających do klas 1-3 szkół podstawowych na terenie dwóch województw: lubelskiego i świętokrzyskiego. Wykorzystano autorski kwestionariusz ankiety. Wyniki. Na podstawie danych zebranych od rodziców, 12% dzieci miało otyłość I stopnia zaś 88% dzieci miało nadwagę. W opinii ponad połowy rodziców - 54,7% (n=41) ich dziecko waży lekko ponad normę. Posiłkiem, który rodzice bardzo często spożywali wraz z dzieckiem była kolacja – 85,3% oraz obiad – 40%. Produkty deklarowane przez rodziców jako obecne w diecie ich rodziny codziennie to najczęściej jasne pieczywo (48%) i wędliny (44%), a spośród napojów herbata (88%). Raz w tygodniu (24%) lub rzadziej (38,7%) pojawiało się w diecie ciemne pieczywo, podobnie kasze – raz w tygodniu (53,3%) i rzadziej (30,7%). Produkty typu Fast-food pojawiają się w diecie rodzin ankietowanych raz w tygodniu (37,3%) lub rzadziej (42,7%). Blisko co trzeci badany (32%, n=24) wskazał, że raczej nie prowadzi rozmowy na temat zdrowego odżywiania ze swoim dzieckiem. Co do form spędzania wolnego czasu wskazywano odpoczynek w domu przed telewizorem lub czytanie książek (60%), zabawa z dzieckiem i pomoc w lekcjach - 62,7% oraz chodzenie na spacery z dzieckiem - 60%. Połowa badanych rodziców zadeklarowała, że zawsze przygotowuje posiłki samodzielnie w domu (50,7%). Wnioski. Ankietowani rodzice dzieci z nadwagą i otyłością nie dostrzegają problemu nadmiernej masy ciała swoich dzieci. Nawyki żywieniowe oraz dotyczące aktywności fizycznej rodzin wymagają korekty. Abstract Introduction. The overweight and obesity among children is today one of the most serious health problems, which should be a call for an action, as e.g. multisectoral programs of health promotion and health education of the family directed to the change of the lifestyle. Aim. To understand and analyse selected elements of the lifestyle of the family with the young school children with the problem of overweight and obesity. Material and Methods. The study was conducted in 2015 among 75 parents (100%) of the young school children with the overweight and obesity in two Polish voivodships: Lubelskie and Świętorzyskie. Self-constructed questionnaire was applied in the study. Results. Based on the data collected from parents, 12% of children had obesity and 88% were overweight. In the opinion of more than half of parents - 54.7%, their child weighs slightly over the norm. The supper (85.3%) and the dinner (40%) were the most often mentioned meals which parents eat with their child. The most often indicated products declared by the parents as present in the diet of their families every day is the white bread (48%) and meat (44%), and tea among drinks (88%). Dark bread appears in the families diet once a week (24%) or less frequently (38.7%), similarly grits - once a week (53.3%) and less frequently (30.7%). Fast-food appear in the diet of families surveyed once a week (37.3%) or less frequently (42.7%). Nearly one third of respondents (32%) do not talk about healthy eating with their child. As for leisure activities, rest at home watching TV or reading books (60%), playing with the child and help with their homework - 62.7%, going for walks with their child - 60% were the most often mentioned. Half of the surveyed parents declared that always preparing meals by their own at home (50.7%). Conclusions. The surveyed parents of children who are overweight and obese do not see the problem of excessive weight of their child. The eating habits and physical activity of families require correction.